The Effect Of Product Innovation And Service Quality On Customer Satisfaction: A Study On Indonesian Sharia Banks - Jumatul Aolia; Putri Aulia; Rosmiati; Herdi Gilang Ananta; Ahadiah Agustina (JPSDa: Jurnal Perbankan Syariah Darussalam, 2025)
This study aims to analyze the effect of product innovation and service quality on customer satisfaction at Islamic banks in Indonesia. The main issue in this study relates to the importance of developing relevant service and product strategies in increasing customer satisfaction and loyalty in the increasingly competitive Islamic banking sector. The approach used is quantitative with descriptive design. Primary data were collected through the distribution of Likert scale questionnaires to 100 randomly selected respondents. The independent variables consist of product innovation (X?) and service quality (X?), while the dependent variable is customer satisfaction (Y). The analysis technique used is multiple linear regression with the help of SPSS software version 22. The results showed that both product innovation and service quality have a significant influence on customer satisfaction, both partially and simultaneously. Simultaneously, the two variables explain 74.7% of the variation in customer satisfaction. The findings confirm the importance of product renewal and service quality improvement as key strategies in strengthening the position of Islamic banks in Indonesia.